Anti-cracking Technology and Application of Fiber Reinforced Concrete on Bridge Deck Pavement - Pang Li guo; Yu Lei; Chai Ming ming; Zhang Biao zhi (E3S Web of Conferences, 2021)
In order to make the bridge deck pavement not easy cracking, the anti-cracking technology is put into effect on a certain bridge. The cementing material is selected after analyzing the theory that how fiber can enhance the concrete anti-cracking performance. The proper fiber is selected by testing and comparing the dispersibility and hydroscopicity of three kinds of fibers. The proper content of fiber is found by test and comparing different fiber contents in the same mix proportion concrete. The fiber is sent into the in forced-mixing concrete plant by spreading the fiber on the crawler belt. The construction technology including slab treatment, transport, pave, vibrate and curing is put forward. After 1 year observing, there is no any cracking on the bridge deck pavement. The life of bridge is increased. The cost of maintain is decreased. The goal of anti-cracking has been achieved.